Preliminary results on the effects of orthopedic implant stiffness fixed to the cut end of the femur on the stress at the stump-prosthetic interface (Fracture and Structural Integrity, 2021)
A lot of trans-femoral amputation patients experience skin breakdown due to the pressures and shear stresses in the stump-prosthesis interface. In this study, a finite element model was employed to investigate the stresses at the stump interface in the case of an orthopedic implant fixed to the cut end of the femur. By changing the stiffness of this implant, we aim to see how the stiffness of this implant affects the stresses in the interface between the amputated limb and the prosthesis. To find out the effects of implant stiffness, five values for the elastic modulus, ranging from 0.1 to 0.5 Mpa, with an interval of 0.1 Mpa were employed in the implant structure of the FE model.Obtained results show that the implant played important role in reducing the stresses at the stump-prosthesis interface where the contact pressure did not exceed 53 Kpa and 17.3 Kpa for shear stress in the stiffer case of an implant, while the contact pressure in the case of femur without implant exceeded 79Kpa and 42 Kpa for shear stress. We also noted that the intensity of the contact pressure and the shear stress is proportional to the stiffness of the implant, as the greater the implant stiffness, the higher the peak of these stresses.
Keywords: Prosthesis; Stump interface; Stiffness; Contacts stresses; Implant